Who cooked Adam Smith's dinner? : a story about women and economics - Marçal, Katrine (Pegasus Books LLC, 2016)
"When philosopher Adam Smith proclaimed that our actions are motivated by self-interest, he used the example of the baker and the butcher to lay the foundations for his "Economic man." He argued that they gave bread and meat for profit, not out of the goodness of their hearts. It's an ironic point of view coming from a bachelor who lived with his mother for most of his life-- a woman who cooked his dinner every night. Nevertheless, Smith's economic man has dominated our understanding of modern-day capitalism, Such a viewpoint disregards the unpaid work of mothering, caring, cleaning, and cooking. Essentially, the father of modern economics has based our whole concept of capitalism on a system that ignores half of its participants. ...Who Cooked Adam Smith's Dinner? charts the myth of the economic man, from its origins at Adam Smith's dinner table to its adaptation by the Chicago School to its disastrous role in the 2008 Global Financial Crisis."--Jacket flap.